Two‐dimensional transthoracic echocardiographic finding of left atrial compression resulting from blunt trauma to the thoracic spine. Issue 12 (20th November 2020) - Gupta, Rakesh; Nanda, Navin C.; Sozzi, Fabiola; Chakraborti, Nandita; Mangla, Sidharth; Gupta, Tanya; Elmarzouky, Zeyad M.; Dulal, Subash
Abstract: We present an adult female in whom two‐dimensional transthoracic echocardiography demonstrated encroachment of the thoracic spine on the left atrium (LA) resulting in a very small, compressed LA cavity by a prominent thoracic spine shadow. Computed tomography (CT) scan of the chest showed compression of the LA produced by localized anterior deformation of the thoracic spine which had resulted from blunt injury to her spine following a fall from a swing several years previously.